Value Added Tax And Minimum Wage Influence On Purchasing Power: Maslahah View - Riska Amaliah; Muhammad Ikhsan Harahap; Nur Ahmadi Bi Rahmani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - The purpose of this study is to determine the influence of Value Added Tax and the City Minimum Wage on the purchasing power of the community in Medan City during the period 2015–2024. Method - This research employs a quantitative approach utilizing secondary data obtained from the Central Bureau of Statistics (BPS) and other official government sources. The dataset for this study comprises all annual data related to Value Added Tax, City Minimum Wage, and public purchasing power in Medan City from 2015 to 2024, resulting in 10 observations. Data analysis was conducted using EViews software to examine the relationships among the variables. Main Findings - The results show that both VAT and CMW meaningfully influence the community’s purchasing power. Increases in VAT and minimum wage adjustments have been shown to affect people’s ability to meet their consumption needs, emphasizing the strategic role of fiscal and labor policies in sustaining public welfare.Theory and Practical Implications - The results show that VAT, which does not have a significant effect on purchasing power, can be positioned as maslahah ‘ammah, with its revenue managed transparently for public benefit. Meanwhile, the minimum wage has a significant effect on purchasing power, so wage policies should be set fairly to safeguard maslahah dharuriyah in fulfilling basic needs.Novelty - The novelty of this research lies in the use of the maslahah perspective in analyzing the simultaneous influence of VAT and minimum wage on the purchasing power of Medan City’s community, thereby providing a new contribution in examining the linkage between fiscal and labor policies with societal welfare.